(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The present article studies English idiomatic expressions containing proper names from a linguo-cognitive perspective. Idioms with onomastic elements represent a culturally and conceptually rich subclass of English phraseology, in which proper names lose their primary referential function and acquire symbolic and generalized meanings. Drawing on data from idiom dictionaries and language corpora, the study analyzes anthroponyms, toponyms, and mythological or biblical names to reveal the cognitive mechanisms underlying their semantic reinterpretation. The analysis demonstrates that idiomatic meaning is motivated by conceptual metaphor, conceptual metonymy, and culturally embedded frames that activate shared background knowledge. The findings highlight the significant role of proper names as cognitive triggers in meaning formation and contribute to a deeper understanding of the interaction between language, mind, and culture. The study also discusses implications for cognitive linguistics, phraseology, language teaching, and intercultural communication.